FINANCIAL LITERACY, IMPULSIVE BUYING, AND FINANCIAL STRESS AMONG GENERATON Z: THE MEDIATING ROLE OF CONSUMER DEBT - Vika Nabilla Amwa; Krisdiana Krisdiana (Universitas KH. Abdul Chalim Mojokerto, 2026)
Advances in digital financial services, especially consumer credit schemes such as buy now, pay later (BNPL), facilitate transactions; however, they also have the potential to cause financial stress if not accompanied by adequate financial literacy and management. This condition is particularly relevant for Generation Z, who have broad access to various digital credit services. This study aims to analyze the influence of financial literacy and impulsive buying behavior on financial stress, with consumer debt as a mediating variable. A quantitative approach was employed through a survey of 150 Generation Z respondents aged 18–27 years in the Cirebon area, selected using purposive sampling. Data were collected באמצעות a Likert-scale questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that financial literacy has a significant effect on financial stress and consumer debt levels. Meanwhile, impulsive buying does not have a direct effect on financial stress but has a significant effect on consumer debt. Furthermore, consumer debt has a significant effect on financial stress and acts as a mediating variable in the relationship between financial literacy and impulsive buying on financial stress. These findings suggest that consumer debt is a key mechanism explaining how financial literacy and consumptive behavior influence the level of financial stress among Generation Z.